Integrating engineering education and humanities for global intercultural perspectives : proceedings of the Conference "Integrating Engineering Education and Humanities for Global Intercultural Perspectives", 25-27 March 2020, St. Petersburg, Russia /: proceedings of the Conference "Integrating Engineering Education and Humanities for Global Intercultural Perspectives", 25-27 March 2020, St. Petersburg, Russia. (2020) - Unknown
No abstract available